Improving outcomes for pancreatic cancer: radical surgery with patient-tailored, surgery-specific advanced haemodynamic monitoring. (30th April 2013) - Weinberg, Laurence; Houli, Nezor; Nikfarjam, Mehrdad
Abstract : Pancreatic cancer has poor prognoses, with a median survival after diagnosis of less than 6 months. For some patients radical surgery remains the only chance of long-term cure. We report the successful outcome of a patient with pancreatic cancer and portal vein encasement that underwent a biliary bypass procedure and chemoradiotherapy. He was reassessed 8 months later where a complete resection of the pancreatic cancer was undertaken. The patient required a total pancreatectomy, splenectomy, subtotal gastrectomy and partial colectomy. Portal and superior mesenteric vein resection was performed, with reconstitution using the splenic vein as conduit with its draining inferior mesenteric vein. We report novel aspects of the surgical technique and describe our institution's patient-tailored, surgery-specific goal-directed strategy that was considered paramount for the successful perioperative outcome in this case.